Analysis of masonry structures: review of and recent trends in homogenization techniques - Lourenço, Paulo B. (2007)
The mechanics of masonry structures have been underdeveloped for a long time in comparison with other fields of knowledge. Presently, nonlinear analysis is a popular field in masonry research and homogenization techniques play a major role despite the mathematical and conceptual difficulties inherent to this approach. This paper addresses different homogenization techniques available in published literature, aiming at defining a first catalogue and at discussing the advantages and disadvantages of the different approaches. Finally, special attention is given to a micromechanical based model and a model based on a polynomial expansion of the microstress field. These seem promising and accurate strategies for advanced structural analysis.